Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Es Krim Mixue (Studi Pada Mahasiswa Manajemen 2019 Universitas Islam Malang) - M Nur Ihsan; Budi Wahono; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted at the Faculty of Economics and Business, Islamic University of Malang, Jl. Major General Haryono No. 193 Lowokwaru District, Malang City, East Java 65144. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of product quality, price and promotion on purchasing decisions. The independent variables used are product quality, price and promotion, the dependent variable is the purchase decision, while the variable. The sample used in this study were 105 respondents who were Mixue Ice Cream consumers. Data collection techniques using a questionnaire. The results of this study indicate that product quality, price and promotion have a direct effect on the purchasing decision of mixue ice cream. Keywords: Product Quality, Price, Promotion and Purchase Decision